Being versus appearing smart: Children's developing intuitions about how reputational motives guide behavior. Issue 2 (15th November 2021) - Good, Kayla; Shaw, Alex
Abstract: Children engage in reputation management to appear favorably to others. The present studies explore when children use reputational motives to predict others' behavior. Four‐ to 9‐year‐old children ( N = 576; 53% female; approximately 60% White) heard stories about two kids: one who cares about being competent, and one who cares about appearing competent. Across five studies, with age, children predicted the reputationally motivated child would be more likely to lie to cover up failure ( OR = 1.97) but less likely to seek help in public (vs. private; OR = 0.53) or downplay success ( OR = 0.66). With age, children also liked this character less ( OR = 0.56). Implications of these findings for children's reputation management and achievement motivation are discussed.